Kepuasan Nasabah dan Dampaknya pada Loyalitas Nasabah Bank Kalsel Cabang Tanjung Kalimantan Selatan - Ariesta Budi; Dwi Wahyu Artiningsih; Taharuddin Taharuddin (Universitas Lambung Mangkurat, 2014)
This study aims to examine the effect of six dimensions of banking service quality of which include effectivities and assurance, access, price, tangibility, reliability service portofolio towards customer satisfaction, and examination on the effectof customer satisfaction on the customer loyalty.The results of this study show that the dimensionsof effectiveness and assurance bring no significant effect on the customer satisfaction where the T-Statistic of 0.331 is below the value of the T-Table of ± 1.652. the dimension of access has a value of T-Statistic 0.422 and has no significant effect on customer satisfaction, the dimension of price has a significant effect on customer satisfaction where the value of T-Statistic is 1.774. the dimension of tangibility has a significant effect on customer satisfaction where the T-Statistic isv 5.043, the dimension of portofolio services significantly influences customer satisfaction where the value of T-Statistic is 2.158, a significant effect on the reliability dimension of customer satisfaction is shown by the T-Statistic value 0f 2.006. Customer satisfaction then found to have a significant effect where the value of T-Statistic is 14,052 which means that the value of T-Statistic > T-table value.This study also results in the findings that tangibilitydimension has a greater influence than five other dimensions of banking services quality. The results of this study confirms the results of previous studies stating that tangibility or in other words physical aspects has a greater influence that deserves greater attention from the management for the sake of increasing the customer satisfaction.Keywords: Quality of Service, Customer Satisfaction, Customer Loyalty